Heat capacity of some terpenes in the temperature range between (293.15 and 353.15) K and at 85.1 kPa - Castellanos Buitrago, Nicolás Stiven (2022)
The heat capacity of several terpenes ((−)-carveol, (1R)-(−)-nopyl acetate, γ-terpinene, carvacrol, 3 carene, (1R)-(−)-myrtenol, (S)-(−)-perillyl alcohol, α-pinene oxide and (+)-limonene oxide) were estimated at Medellín (Colombia) atmospheric pressure and in the temperature range from 293.15 K to 353.15 K with a heating rate of 0.5 K/min. All measurements were performed by means of a Setaram E/μDSC 7 Evo-1A microcalorimeter. Heat capacities dependence with temperature were fitted to a third order polynomial equation. Furthermore, heat capacities were estimated using group contribution with Dvorkin et al model, the Dadgostar–Shaw universal correlation and a modified correlation of Dadgostar-Shaw and compared with experimental data. The reliability of the results was evaluated using water as a known substance; the experimental uncertainty measured using naphthalene was lower than 1.5 %.